2017
DOI: 10.1021/acssuschemeng.7b01682
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Low Concentration Rare Earths from Leach Solutions of Ion-Adsorption Ores by Bubbling Organic Liquid Membrane Extraction Using N1923

Abstract: A new bubbling organic liquid membrane extraction using primary amine N1923 at large 24 aqueous-to-oil phase ratios was suggested to extract and enrich extremely low concentration rare 25 earths from the acidic sulfate leach solutions of ion-absorbing type rare-earth ores. It was revealed 26 that bubbling organic liquid membrane extraction was in fact an interfacial chemical reaction of 27 organic extractant molecules absorbing at the surface of organic liquid membrane supported by gas 28 bubbles with the targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Considering the economical and technological feasibility of step-leaching and pre-enrichment of light and heavy REEs from Kao/Mt, the influence of desorption agent pH, concentration, and contact time on desorption characteristics of Nd 3+ , Eu 3+ , and Lu 3+ was investigated. Ammonium sulfate was selected as the desorption agent, which is commonly found in ion-adsorption RE ores . Since ion-adsorption RE ores are formed in a slightly acidic medium, the adsorbents that were used in the following desorption experiments were synthesized in a pH 5 solution.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the economical and technological feasibility of step-leaching and pre-enrichment of light and heavy REEs from Kao/Mt, the influence of desorption agent pH, concentration, and contact time on desorption characteristics of Nd 3+ , Eu 3+ , and Lu 3+ was investigated. Ammonium sulfate was selected as the desorption agent, which is commonly found in ion-adsorption RE ores . Since ion-adsorption RE ores are formed in a slightly acidic medium, the adsorbents that were used in the following desorption experiments were synthesized in a pH 5 solution.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Ammonium sulfate was selected as the desorption agent, which is commonly found in ion-adsorption RE ores. 31 Since ion-adsorption RE ores are formed in a slightly acidic medium, the adsorbents that were used in the following desorption experiments were synthesized in a pH 5 solution.…”
Section: Adsorption Characteristics Of Nd 3+mentioning
confidence: 99%
“…Some studies dealing with the extraction and separation of REEs used liquid membranes [16]. A bubbling organic liquid membrane extraction using primary amine N1923 was used to extract and enrich low concentration REEs from leaching solutions of rare-earth ores [17]. Low-concentration REEs were also extracted using a bubbling organic liquid membrane with un-saponified P507 [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, it was found that a prerequisite for successfully performing the bubbling organic liquid membrane extraction is the method to control the formation of stable organic liquid membrane covered on the surface of gas bubbles . When the gas was bubbled into the aqueous solutions through the internal gas needles of the injector, the organic extractant passed through the annular gaps between the internal gas needles and the external organic needles and then met with the gas bubbles on the top end of the gas needles, so that the organic extractant could be dispersed and spread on the surface of the gas bubbles because of its surface activity.…”
Section: Introductionmentioning
confidence: 99%